Approaches To Improve Safety And Recover Lost Productivities In Vertical Shaft Sinking By Making Use Of Industrial Engineering And Risk Driven 3-D Modelling Techniques - 1. Synopsis - T. E. Wakefield (The Southern African Institute of Mining and Metallurgy, 2009)
Over several decades in Southern Africa the advance rates when sinking vertical shafts have declined significantly. The upside has been a substantial improvement in shaft bottom conditions and a commensurately improved safety performance, with an increasing number of shafts being sunk without fatalities and disabling injuries. This paper briefly reviews historical sinking rates and matches changed sinking productivity to the introduction of new sinking methods that have been adopted to eliminate/mitigate safety risks. Meeting the challenge of returning to historical advance rates whilst progressing in the quest for zero harm by utilizing three dimensional animated computer modelling is described. Making use of commercial modelling software makes it easier to evaluate different methods, sequencing, in shaft barrel ergonomics, and stage and shaft bottom layouts before procuring project plant and equipment. Benefits accrue not only in better communicating methods and configurations for detailed planning and design, but also during crew training. The traditional engineering ?as-built? drawing practice has been extended to the concept of an ?as executed? sinking model which seeks to capture operational experience and learning for future best practice. The paper concludes with some of the organizational culture challenges being overcome as this non traditional approach to shaft sinking optimization is being introduced.